Propaganda dan Ideologi dalam Iklan Politik di Media Sosial - Alvina Juniasari; Arfian Suryasuciramdhan; Amelia Putri; Emilya Yohana; Endang Wiguna (International Forum of Researchers and Lecturers, 2025)
As the largest political event in Indonesia, elections are closely tied to mass political communication strategies. In the digital era, social media has emerged as a new arena for political actors to convey campaign messages. This study examines how propaganda techniques are applied in political advertisements on social media, focusing on the dynamics between manipulation and persuasion efforts targeting voters. Through a literature review of various journals and reports, this paper explores forms of propaganda, visual symbolism, celebrity involvement, and regulatory issues concerning political advertisements on social media. The findings indicate that propaganda techniques in digital ads not only appeal to voters' emotions but also create spaces for bias and misinformation that can disrupt the quality of democracy.​